"Trojan Horse" Effect in Photocatalysis–How Anionic Silver Impurities Influence Apparent Catalytic Activity. Issue 10 (23rd January 2017) - Kaufhold, Simon; Petermann, Lydia; Sorsche, Dieter; Rau, Sven
Abstract: The problematic consequences of using silver carbene precursors for the synthesis of NHC‐complexes is elucidated with the example of dinuclear Ru–Rh/Ir photocatalysts. The presence of silver in the products is proven and an alternative silver‐free synthetic approach successfully implemented. A significant difference in performance in photocatalytic hydrogen evolution reactions of catalysts generated by the different strategies is observed. Abstract : Small amount but a large impact : Identical photocatalysts showed severe differences in catalytic performance depending on utilization or avoidance of silver in the synthetic strategy.